Evaluating relational repair work with infants and mothers impacted by family violence. Issue 1 (March 2016) - Bunston, Wendy; Eyre, Kathy; Carlsson, Anthony; Pringle, Kristen
This paper describes the delivery of a therapeutic infant/mother group work intervention program called The Peek-a-Boo ClubTM, which ran from mid-2005 until early 2012. It examines the importance of intervening early with infants and mothers impacted by family violence. The intervention used an 'infant led' approach to facilitate the repair of relational ruptures in the infant/mother attachment as a consequence of experiencing family violence. It provides an overview of the intervention and work undertaken to enhance the quality of the attachment between mothers and their infants. In particular, it presents the demographic data of 128 mothers and their infants who participated over a specific period (2007–2011) and then the results of a small quantitative pre- versus post-pilot evaluation of 30 groups over this same time period. Further qualitative data is also included. The challenges and complexities involved in collecting data from this 'hard to reach', ambivalent and vulnerable client group are discussed. The results of the evaluation indicate some limitations in the methodology, however, overall The Peek-a-Boo ClubTM program was associated with improved scores on outcome measures assessing infant, mother and infant–mother functioning. Though only a small study, it supports intervening early to assist mothers and infants impacted by family violence in order to repair relational disruption, and encourage mother's availability to respond sensitively to their infant's efforts in managing affect regulation. A more comprehensive, tailored and systematic evaluation of such interventions is recommended.